
On 8/24/12 3:44 AM, Sebastien Zany wrote:
More specifically (assuming I understood the statement correctly):
Suppose I have two base functors F1 and F2 and folds for each: fold1 :: (F1 a -> a) -> (μF1 -> a) and fold2 :: (F2 a -> a) -> (μF2 -> a).
Now suppose I have two algebras f :: F1 μF2 -> μF2 and g :: F2 A -> A.
When is the composition (fold2 g) . (fold1 f) :: μF1 -> A a catamorphism?
From http://comonad.com/haskell/catamorphisms.html we have the law: Given F, a functor G, a functor e, a natural transformation from F to G (i.e., e :: forall a. F a -> G a) g, a G-algebra (i.e., f :: G X -> X, for some fixed X) it follows that cata g . cata (In . e) = cata (g . e) The proof of which is easy. So it's sufficient to be a catamorphism if your f = In . e for some e. I don't recall off-hand whether that's necessary, though it seems likely -- Live well, ~wren